THE ROLE OF ADAPTIVE LEARNING IN THE EDUCATION SYSTEM (Web of Teachers: Inderscience Research, 2026)
This article examines adaptive learning. It defines and explains the reasons for adapting learning to the student. It also describes in detail the use of adaptive learning in the educational system, its implementation, and the results.